IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN IPA; STUDI KASUS DI MI ROUDLOTUL ULUM SURABAYA - Syamsudin Syamsudin; Luluk Safitri; Musdalifah Musdalifah (Universitas Islam Lamongan, 2019)
This research aims to know how the science learning process in the implementation of the 2013 curriculum at MI Roudlotul Ulum Surabaya. This research focuses on the process of planning, implementing, and evaluating outcomes and obstacles faced by the teacher in implementing science learning of the 2013 curriculum. The method used in this research is qualitative descriptive. The data analysis in this study is reducting data, presenting data, and drawing conclusions. Based on the data analysis it can be concluded that the science learning in implementing of 2013 curriculum in MI Roudlotul Ulum Surabaya uses the scientific method. Moreover, the assessment uses authentic assessment that is consistent with the 2013 curriculum which includes aspects of attitude, aspect of knowledge, and aspect of skills. The obstacle faced by teachers in the learning process is students have a different absorption and understanding of a teaching material. It can be overcome by guiding by the teacher when guiding work in a group